Rotationplasty for Severe Congenital Femoral Deficiency - Corey B. Fuller; Craig H. Lichtblau; Dror Paley (MDPI AG, 2021)
Rotationplasty is a reconstructive option for severe congenital femoral deficiency (CFD). The senior author (D.P.) developed five new rotationplasty techniques for use in CFD based on the Paley classification, including the Paley-Brown (fusion femur to pelvis), Paley (fusion femur to femoral head), Paley-Winkelman (insertion tibial condyle to acetabulum), PaleySUPERhip-Van Nes (hip osteotomy with knee fusion) and PaleySling-Van Nes (hip reconstruction with knee fusion revision) rotationplasty techniques. The purpose of this study is to retrospectively evaluate the complications, radiographic outcomes and need for secondary surgery in 19 rotationplasty cases performed by the senior author (D.P.) for severe CFD from 2009 to 2019. Rotationplasty comprised only 2% of the authors treated CFD cases during this period. Average age at surgery was 8.6 years old. Average follow-up was 3.3 years. Sixteen concomitant procedures were performed including temporary arthrodesis, tibial osteotomy and SUPERhip procedure. The most common complication was wound necrosis/dehiscence, which occurred in 52% of the cases related to the circumferential incision and required a total of 31 additional debridements. Additional complications were successfully treated and included sciatic nerve palsy decompressed by abducting the femur, a tibial delayed union that underwent bone grafting, two distal femur failed epiphysiodesis treated by revision with one osteotomy and a thigh compartment syndrome requiring debridement. Indication specific rotationplasty successfully addresses the severe degree of femoral deficiency, deformity, and discrepancy in patients with CFD, despite high rates of wound complications.